Future research into the treatment of vitiligo: where should our priorities lie? Results of the vitiligo priority setting partnership - Eleftheriadou, V (Blackwell Publishing Ltd, 2011)
BACKGROUND: Vitiligo is the most frequent depigmentation disorder of the skin and is cosmetically and psychologically devastating. A recently updated Cochrane systematic review ‘Interventions for vitiligo’ showed that the research evidence for treatment of vitiligo is poor, making it difficult to make firm recommendations for clinical practice. OBJECTIVES: To stimulate and steer future research in the field of vitiligo treatment, by identifying the 10 most important research areas for patients and clinicians. METHODS: A vitiligo priority setting partnership was established including patients, healthcare professionals and researchers with an interest in vitiligo. Vitiligo treatment uncertainties were gathered from patients and clinicians, and then prioritized in a transparent process, using a methodology advocated by the James Lind Alliance. RESULTS: In total, 660 treatment uncertainties were submitted by 461 participants. These were reduced to a list of the 23 most popular topics through an online/paper voting process. The 23 were then prioritized at a face-to-face workshop in London. The final list of the top 10 treatment uncertainties included interventions such as systemic immunosuppressants, topical treatments, light therapy, melanocyte-stimulating hormone analogues, gene therapy, and the impact of psychological interventions on the quality of life of patients with vitiligo. CONCLUSIONS: The top 10 research areas for the treatment of vitiligo provide guidance for researchers and funding bodies, to ensure that future research answers questions that are important both to clinicians and to patients.